Fenomena Overthinking pada Remaja Muslim dalam Perspektif Was-Was: Dampaknya terhadap Kesejahteraan Spiritual - Muhamad Hafidz Wahyudin; Vismaia Nur Fitriani; Astuti Darmiyanti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study describes overthinking among Muslim adolescents from the perspective of was-was and analyzes its impact on spiritual well-being. The issue is important because repetitive negative thinking in adolescence may appear not only as psychological worry, but also as religious doubt, excessive fear of sin, and uneasiness in worship. This study used a qualitative descriptive design with a phenomenological orientation. Data were collected through semi-structured interviews, simple observation, and field notes involving eight Muslim adolescents aged 15-18 years. Data analysis was conducted thematically through coding, theme grouping, interpretation, and source triangulation. The findings show that overthinking appears as repetitive thoughts about past mistakes, anxiety about the future, fear of disappointing parents, and doubt about the validity of worship. From the perspective of was-was, these experiences are reflected in repeated doubts about intention, ablution, prayer recitation, and whether worship is accepted by Allah. The impact on spiritual well-being includes reduced inner peace, disturbed concentration in worship, excessive guilt, and a temporary weakening of perceived closeness to Allah. The study implies the need for balanced religious guidance, family support, and spiritual counseling that helps adolescents distinguish carefulness in worship from excessive was-was.